Beyond `crude pragmatism` in sports coaching: Insights from C.S. Peirce, William James and John Dewey: A Commentary - Devine, J. W.; Knight, C. J. (International Journal of Sports Science & Coaching, 2017)
Jenkins proposes that coaches should engage in `legitimate philosophical thinking`. In essence, he suggests that coaches should put the Philosophy (back) into coaching philosophy. We have supported this proposal, but we have suggested that the best way to achieve this is to advance a virtue-based rather than pragmatic study of coaching. Such an approach provides a clear pathway and menu of questions for coaches to begin thinking philosophically. It concerns the virtues of a good coach generally, not merely the intellectual virtues of a good coach. It is capable of making sense of integrity, and virtue ethics does not come with the many and varied wider philosophical commitments associated with philosophical pragmatism. In short, we can put the Philosophy back into coaching philosophy in the way that Jenkins suggests without having to swallow the heady brew of philosophical pragmatism. FROM AUTHOR